The gender dimensions of drought in Fedis Woreda District, Ethiopia - Diletta Carmi (United Nations Research Institute for Social Development (UNRISD), 2016)
This paper presents the key findings of a research project that investigated women's and men's vulnerability to drought in Fedis woreda, a district located in Eastern Ethiopia. It focuses on the gendered impacts of drought on rural livelihoods in dryland areas. The research used a comparative assessment of both men's and women's susceptibility and coping capacities. Findings show that, in the event of a drought, women's workload increases, their health is severely compromised due to reduced food intake, girls are more likely to drop out of school, and women have fewer chances than men to engage in income-generating activities. In addition, women do not have decision-making power on many issues that impact livelihood security, such as crop cultivation, agricultural practices and asset management. As a result, women's capacity to reduce the negative consequences of drought, be it preventive or palliative, is inferior to that of men. Furthermore, this paper analyses the government's key interventions to reduce drought risk. The analyses of these different aspects illustrate that women are more likely than men to experience harm from drought. The paper therefore calls for stronger and gendersensitive risk reduction measures that take into consideration women's needs and their disadvantaged position.
Additional information: Prepared for the UNRISD project on: Gender Dimensions of Food and Water Security in Dryland Areas
Keywords: 330